2013
DOI: 10.1108/ecam-01-2012-0002
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of safety advisor roles and site safety performance

Abstract: Purpose -Present findings from a UK study, funded by the Institution of Occupational Safety and Health (IOSH), on the relationship between safety advisor roles and safety performance. Design/methodology/approach -Roles and organisational factors for contractors' safety advisors (independent variables) were derived from existing literature. The dependent variable was "safety performance", measured by accident incidence rate (AIR). Data were provided by 101 contractors and variance of means analysis was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Some organizational structure attributes directly shape the role and effectiveness of safety professionals including whether they are internal resources or external consultants, organizational proximity to senior management, their formal line of report, and the amount of personnel and financial resources. Cameron, Hare et al (2013) found organizations that relied solely on external consultants rather than internal safety professional resources had three times higher accident rates. This finding is consistent with previous studies (Hinze 2002), and Hale (1995) suggested that external resources cannot effectively understand the organizational context or adequately influence company policy.…”
Section: Safety Structurementioning
confidence: 97%
See 3 more Smart Citations
“…Some organizational structure attributes directly shape the role and effectiveness of safety professionals including whether they are internal resources or external consultants, organizational proximity to senior management, their formal line of report, and the amount of personnel and financial resources. Cameron, Hare et al (2013) found organizations that relied solely on external consultants rather than internal safety professional resources had three times higher accident rates. This finding is consistent with previous studies (Hinze 2002), and Hale (1995) suggested that external resources cannot effectively understand the organizational context or adequately influence company policy.…”
Section: Safety Structurementioning
confidence: 97%
“…An independent matrix style of organization with dual authority structures is more likely to accept challenge and leverage it to improve (King 1999). Cameron, Hare et al (2013) found that the formal authority of the safety professional was related to improved safety performance, and in all cases where safety professionals saw themselves as having authority; they also held a senior position.…”
Section: Safety Structurementioning
confidence: 97%
See 2 more Smart Citations
“…The practice of having specific safety advisors or similar roles on-site to coordinate and safeguard contractors was explored by Cameron et al (2013). The study showed that contractors hiring external safety consultants had an Accident Incidence Rate (AIR) almost three times higher than those that employed internal safety personnel.…”
Section: Safety Managementmentioning
confidence: 99%